The Influence of the Realistic Mathematics Education (RME) Model on Sixth Grade Students’ Higher HOTS Problem-Solving Ability at SD Negeri 2 Masbagik Timur - Husnan, Muhamad; Husni, Muhammad; Yazid, Muh.; Aziz, Abdul (Pendidikan Islam Anak Usia Dini STIT Palapa Nusantara, 2025)
This study addresses the limited implementation of the Realistic Mathematics Education (RME) model in primary schools, despite its proven potential to enhance students’ higher-order thinking skills (HOTS) and problem-solving abilities. The research aimed to evaluate the effectiveness of the RME model in improving mathematics learning outcomes among sixth-grade students at SD Negeri 2 Masbagik Timur during the 2025/2026 academic year. A quantitative experimental design was employed, involving 18 purposively selected students. Data were collected using validated and reliable pretest and posttest instruments. Statistical analysis included descriptive statistics, normality testing, paired sample t-tests, and effect size measurement. Results indicated a significant improvement in students' performance, with the mean posttest score (M = 72.36) notably higher than the pretest score (M = 53.19). The paired t-test confirmed this improvement as statistically significant (t = -6.774, p < 0.001), while the effect size analysis yielded a very large Cohen’s d value of 1.60. These findings demonstrate that the RME model effectively enhances mathematical achievement, particularly in students’ ability to interpret problems, develop solution strategies, and critically assess outcomes. The study concludes that embedding realistic and contextualized problems into mathematics instruction significantly promotes student-centered learning and strengthens HOTS-oriented problem-solving capabilities. It recommends that educators and curriculum designers adopt RME-based approaches to foster more meaningful and active learning environments. Future research should consider larger sample sizes and longitudinal designs to assess the long-term impact and generalizability of RME implementation.